2018
DOI: 10.1111/rode.12573
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and income inequality: New macrolevel evidence

Abstract: This paper addresses the empirical question of whether microfinance has any impact on income inequality at the macrolevel. Very little research has been conducted on the relationship between the macrolevel scale of microfinance and income inequality over time in a country and across countries. Based on panel‐data techniques, with annual data from 85 countries from 2001 to 2012 and a broad theoretical framework on microfinance and inequality, we provide empirical evidence that suggests that increases in the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 61 publications
5
17
0
Order By: Relevance
“…Population refers to the population growth rate. Robust standard errors in parentheses: ***p < 0.01, **p < 0.05, *p < 0.1. financial inclusion (Mookerjee and Kalipioni 2010; Kim 2016; Park and Mercado 2018; Turégano and Herrero 2018) or microfinance (Kai and Hamori 2009;Hermes 2014;Lacalle-Calderon et al 2019). Our results are also in line with those of single-country studies that have found a negative relationship between household financial inclusion and (income or consumption) inequality in developing countries, such as Bangladesh (Khandker 2005;Mahjabeen 2008) and China (Zhang and Posso 2019).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Population refers to the population growth rate. Robust standard errors in parentheses: ***p < 0.01, **p < 0.05, *p < 0.1. financial inclusion (Mookerjee and Kalipioni 2010; Kim 2016; Park and Mercado 2018; Turégano and Herrero 2018) or microfinance (Kai and Hamori 2009;Hermes 2014;Lacalle-Calderon et al 2019). Our results are also in line with those of single-country studies that have found a negative relationship between household financial inclusion and (income or consumption) inequality in developing countries, such as Bangladesh (Khandker 2005;Mahjabeen 2008) and China (Zhang and Posso 2019).…”
Section: Resultssupporting
confidence: 88%
“…Using all major measures of financial inclusion -including the extent of account ownership and SME lending, as well as the financial inclusion indices developed by Sarma (2012) and Cámara and Tuesta (2014) - Turégano and Herrero (2018) provide further evidence that countries with a more inclusive financial system tend to have a less unequal income distribution. Likewise, studies with a narrower focus on the role of microfinance as a tool for financial inclusion show that the level of income inequality is lower in developing countries where the level of participation in microfinance programmes is higher (Kai and Hamori 2009;Hermes 2014;Lacalle-Calderon et al 2019).…”
Section: Financial Inclusion and Income Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The present study employed the Binary Logistic Model [43][44][45][46] to investigate the effect of socioeconomic variables including financial inclusion on socioeconomic disaster risks (economic poverty and multidimensional poverty) in the study area. The binary logistic regression model is presented below:…”
Section: Determinants Of Socioeconomic Disasters (The Logit Model)mentioning
confidence: 99%
“…The subject of poverty and inequality still one of the most problems that constitute a major anxiety in the topic of economic development, in particular by poor developing countries during the last decades. For that reason, understanding the key role played by micro nance program innovation in reducing poverty and inequality is a question of great concern for developing countries' poor population where providing nancial access, like micro nance, to the poorest seems to be a panacea for reducing poverty (Johnson & Rogaly, 1997;Armendariz & Morduch, 2005;Beck, 2007;Hossain & Knight, 2008;Bakhtiari, 2011;Gibbons & Meehan, 2002, Imai et al 2012Roodman & Morduch, 2014;Bel hadj Miled & Ben Rejeb, 2018) and income inequality (Beck et al, 2004;Kai & Hamori, 2009;Tchouassi, 2011;Hermes, 2014;Bangoura et al, 2016;Lacalle-Calderon et al, 2019). The micro nance industry carries every sign of an innovation in its take-off phase (Mersland & Strøm, 2012).…”
Section: Introductionmentioning
confidence: 99%